Silicon-based microring resonators for multi-solitons generation for THz communication - Amiri, I.S.; Ahmad, Harith; Ghasemi, M.; Ismail, Mohammad Faizal; Aidit, S.N.; Soltanian, M.R.K.; Nafarizal, N. (Springer, 2016)
Silicon-based microring resonator (SMRR) is required to select the specific channels in a wavelength division multiplexing systems. SMRRs also have applications in optical filters, data storages and bio-sensors, due to their significant advantages such as versatile wavelength-selective elements, compact size, fast operation and compatibility with current optical infrastructure, as well as being able to divert groups of inputs light and synthesize a wide class of filter functions. Here, we proposed a system for multiple mode-locked soliton generation, where the photonic circuits simulator PICWave software made by photon design based on the time-domain travelling wave method is used for modeling passive and active photonic circuits. A mode-locked spectrum possessing a spacing of 30 ps and a full width at half maximum (FWHM) of 10 ps was generated and input into the ring system. The subsequent multiple mode-locked soliton pulses had a free spectral range of 25 GHz and FWHM of 630 MHz, which corresponded to 0.2 nm and 5 pm respectively, with a 40 ps pulse duration and 200 GHz repetition. The obtained finesse was approximately 39.7, and the Q-factor was approximately 3 × 105.